Ethics Committees: From Ethical Comfort to Ethical Cover - Annas, George J. (The Hastings Center report, 1991)
With this issue George Annas contributes his last At Law to the Hastings Center Report. Since the column was inaugurated in 1976 as Law and the Life Sciences, George has charted the course of biomedical ethics in the courts, challenging readers to come to grips with an emerging body of law in provocative analyses of critical decisions. As he retires from this column we wish him well, and look forward to his continued contributions to our pages. In bidding farewell to one friend we are nonetheless pleased to welcome another as Alexander Morgan Capron, Henry W. Bruce University Professor of Law and Medicine at the University of Southern California and codirector of the Pacific Center for Health Policy and Ethics, joins the Report in the September-October issue as a regular contributor to this column. Prof. Capron, formerly executive director of The President's Commission for the Study of Ethical Problems in Medicine and Biomedical and Behavioral Research, is a distinguished scholar and writer well known to our readers. We welcome the opportunity to share his insights on issues before courts and legislatures nationwide.